Biodistribution of the Radiopharmaceutical Technetium- 99m-Sodium Phytate in Rats After Splenectomy - Pereira, Kércia Regina Santos Gomes (2008)
Drugs and surgery can interfere with the biodistribution of radiopharmaceuticals and data about the effect of splenectomy on the metabolism of phytate-Tc-99m are scarce. This study aimed at evaluating the interference of splenectomy on phytate-Tc-99m biodistribution and liver function in rats. The SP group rats (n=6) underwent splenectomy. In group C (control) the animals were not operated on. After 15 days, all rats were injected with 0.1mL of Tc-99m-phytate via orbital plexus (0.66MBq). After 30 minutes, liver samples were harvested, weighed and the percentage of radioactivity per gram (%ATI-g) was determined by a Wizard Perkin-Elme gama counter. The ATI%-g in splenectomized rats (0.99±0.02) was significantly higher than in controls (0.4±0.02), (p=0.034). ALT, AST and HDL were significantly lower in SP rats (p= 0.001) and leukocytosis was observed in SP rats. In conclusion, splenectomy in rats changed the hepatic biodistribution of Tc-99m-phytate and liver enzimatic activity